Implementasi Pengajaran Ibadah Pada Anak Berkebutuhan Khusus (Studi Kasus: Sekolah Luar Biasa PGRI Dlanggu) - Al Azizi, Lailatul Africha; Yaqin, Ainul; Rozi, Syaikhu (Philosophiamundi, 2024)
Every Muslim individual is required to perform worship according to the law. This fundamental obligation must not be ignored, including for children with special needs (ABK). Obligatory worship is a form of obedience and devotion to God and is the main foundation in religious life. The 1945 Constitution, the Child Protection Law, and the Law on Persons with Disabilities have mandated the rights of ABK to receive education, including religious education. Religious education, especially worship that is carried out daily, is an important part of the spiritual and moral development of ABK. Providing worship teaching to ABK, who have diverse characteristics, certainly has its steps. This study aims to describe the implementation of worship teaching for deaf-mute, mentally retarded, and autistic students at SLB PGRI Dlanggu. Through a case study approach, this study found that worship teaching is adjusted to the abilities of each student and involves collaboration between teachers, parents, and other students. The study results indicate that worship teaching can run effectively and benefit students socially. Based on these findings, the study recommends increasing support from various parties, such as principals, teachers, universities, and the government, to ensure improving the quality of religious instruction for students with special needs